KONDISI MORFOLOGI CEKUNGAN BANDUNG DAN KARAKTERISITIK BATUAN SEDIMEN SUNGAI CIBOGO KECAMATAN BANDUNG BARAT PROVINSI JAWA BARAT - Ilham Gusrianda; Annisa Putri Amalia; Zahraini Hasriani; Anggi Erliza; Tika Oktavia; Ivana Inggriani; Sovi Rachman; Yunita Aulia Hutabarat; Allan Kurniawan; Jecky Jecky; Triyatno Triyatno (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This research to determine the morphology of the Bandung Basin and determine the characteristics of sedimentary rocks in the Cibogo River. The research method used is descriptive qualitative. Qualitative descriptive analysis in this study starts from determining the process of taking sedimentary rocks and sedimentary rock descriptions by megaskopis. The results of this study show the Bandung Basin morphology, there are 11 landform units, namely Alluvial Fan, Floodplain, Volcanoes, Lava Flow, Anticline Ridge, Lava Flow, Alluvial Volcano Fan, Denudasional Hills, Mountains or Plato Hills and Footslope Slopes. Sedimentary rocks found in the Cibogo River can be classified into two, namely sandstone and clay stone. In observations in the field the sedimentary rocks are non kabonatan which when dripped with 0.1 N HCl liquid to the sedimentary rocks, does not show a reaction or is not bubbly, this shows the sedimentary rocks have low or no carbonate content.